Rencana Bisnis Jasa Maklon Kosmetik PT Asia Chemie Indonusa - Surya Ardi; Carunia Mulya Firdausy (Universitas Tarumanagara, 2022)
PT Asia Chemie Indonusa plans to build a cosmetic factory with Original Equipment Manufacturer (OEM) service as the main business. The company does not have a business plan. The study aims to make a business plan for cosmetic OEM service for PT Asia Chemie Indonusa. The business plan is needed so that this company can run, survive and gain market share in the competitive cosmetic OEM services business so that it can provide good profit and competitive advantages. Qualitative and quantitative analyzes are used in analyzing this business plan. Qualitative analysis tools such as industry analysis (Porter's five strengths), marketing mix, segmentation, targeting, positioning, and SWOT. Quantitative analysis tools such as projected income statements, Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), and Profitability Index (PI). When viewed from a financial perspective, with an investment of IDR 3,000,000,000, the NPV value is IDR 15,613,709,317 (NPV> 0), PI is 6.2 (PI> 1), IRR is 74.8%, and PP is IDR 2.4 years, the study showed that the cosmetic OEM services business project of PT Asia Chemie Indonusa is a feasible investment project. Before building a business, an entrepreneur is advised to make a business plan in advance to find out, analyze and measure whether the business is feasible or not. PT Asia Chemie Indonusa berencana untuk membangun bisnis pabrik penyedia jasa maklon kosmetik, namun perusahaan ini belum mempunyai rencana bisnis. Penelitian ini bertujuan untuk membuat rencana bisnis jasa maklon kosmetik PT Asia Chemie Indonusa. Rencana bisnis ini diperlukan agar perusahaan ini dapat berjalan, bertahan serta mendapatkan pangsa pasar dalam persaingan bisnis jasa maklon kosmetik sehingga dapat memberikan keuntungan yang baik dan berdaya saing. Analisis kualitatif dan kuantitatif digunakan dalam menganalisis rencana bisnis ini. Alat analisis kualitatif seperti analisis industri (lima kekuatan Porter), bauran pemasaran, segmentasi, penargetan, positioning, dan SWOT. Alat analisis kuantitatif seperti proyeksi laporan laba rugi, Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), dan Profitability Index (PI). Bila dilihat dari sisi keuangan, dengan investasi sebesar Rp 3.000.000.000,- maka nilai NPV senilai Rp 15,613,709,317,- (NPV>0), PI senilai 6,2 (PI>1), IRR senilai 74,8%, dan PP senilai 2,4 tahun, maka dapat ditarik kesimpulan bahwa proyek bisnis jasa maklon kosmetik PT Asia Chemie Indonusa layak untuk dijalankan. Sebelum membangun bisnis, seorang pengusaha disaranakan untuk membuat rencana bisnis terlebih dahulu untuk mengetahui, menganalisis dan mengukur apakah bisnis tersebut layak dijalankan atau tidak.